Measuring mangrove-fishery benefits in the Peam Krasaop Fishing Community, Cambodia. (5th January 2021) - Seary, Rachel; Spencer, Tom; Bithell, Mike; McOwen, Chris
Abstract: Whilst previous studies have applied economic value to the ecosystem services mangroves provide to fisheries, most quantitative studies in the peer reviewed literature have limited their measurements to the value provided through a single fishing sector, gear or particular target species group. It can be argued that present research into mangrove-fisheries has not yet represented the full complexity that mangrove-fisheries can encompass in terms of the wide range of people and activities that benefit from the mangrove ecosystem. The reported values of mangroves to fishing livelihoods are therefore likely to fall short of a full valuation. The study provides an all-encompassing value of mangrove benefits to fishing, purposefully investigating the value gained from mangroves through all fishing sectors, fishing activities and target species existing in the Peam Krasaop Fishing Community (PKFC), Koh Kong Province, southwest Cambodia. The ecosystem service value of mangroves for fishing to households in the PKFC was calculated using daily landings volumes collected through semi-structured interviews with fishers, scaled to approximated annual catches. Catch figures were converted to economic value, based on the local market prices given by respondents. Results suggested that the PKFC derives approximately 90% of fishing catch, and 85% of gross income, from mangrove-associated species. Fishing activities are diverse within households; they conduct between 1 and 8 different seasonal fishing activities, spread across mangrove gathering, fishing by boat and mariculture. This study provides a higher estimated proportion of mangrove-associated catches than many studies of fishing communities elsewhere. It may be the case that the PKFC does not have higher levels of mangrove dependency than other mangrove-fisheries. Rather, this study may provide a better quantification of mangrove value than has previously been achieved. Further studies along the same lines, taking a similarly holistic approach to mangrove-fishery valuation, are necessary to test this proposition. Highlights: Quantifications of mangrove benefits to fisheries have been limited in their scope. A holistic quantification of mangrove benefits for fishing was conducted. The Peam Krasaop Fishing Community conduct fishing, gathering and mariculture. Seasonal mangrove-fishing strategies include up to 8 different activities. 90% of catch and 85% of gross fishing income was from mangrove-associated species.